Sistem Pemerintahan pada Keraton Pajang 1546-1586 M - Am'mar Abdullah Arfan (Jurnal Tamaddun: Jurnal Sejarah dan Kebudayaan Islam, 2022)
The existence of the Pajang kingdom in Indonesian history does not have an adequate place in Indonesian historiography. Based on the records of a sailor named Sir Frances Drake who stopped by at Blambangan in 1580 that on the island of Java there were many small kings and all of them were loyal to Pajang as the supreme ruler at that time. This paper will discuss the strategy of the reign of Sultan Pajang, namely Sultan Hadiwijaya who succeeded in becoming a unifier of the kingdom on the island of Java. This research will use library research, namely studying, reviewing, and discussing literature related to the discussion of the strategy of the Sultan Hadiwijaya government. The research method is a historical method consisting of heuristics, verification, interpretation, and historiography so that a chronological and systematic description of events is obtained in by historical facts.